(untitled) (Communications in Mathematical Research, 2021)
In this paper, the boundedness of commutators generated by the n-dimensional fractional Hardy operators and Lipschitz functions on p-adic function spaces are obtained. The authors show that these commutators are bounded on Herz space and Lebesgue space with suitable indexes. Moreover, the commutator of Hardy-Littlewood-Polyá operator is also considered.